How does the dual policy—the C-DRG-based reimbursement system and subsidy policy for appropriate Traditional Chinese Medicine (TCM) techniques—influence physicians’ choice of disease treatment methods in TCM hospitals? - Jin Zhang; Junfeng Liu; Lingfei Qu; Zihao Duan (Health Economics Review)
Abstract Background This study investigates the impact of the diagnosis-related group (DRG) reimbursement system and subsidy policies on the treatment methods of traditional Chinese medicine (TCM) orthopaedic physicians. The objective is to determine the optimal subsidy amount to maximize the number of treated patients. Methods Using Evans’ profit maximization theory, the study examines the intrinsic motivations behind physicians’ behaviours and their influence on the medical market. A discontinuous time series analysis evaluates the effects of the C-DRG-based reimbursement system and subsidies on the number of treated inpatients and inpatient expenses in TCM orthopaedics. Results The expanded implementation of the C-DRG-based reimbursement system substantially boosted both orthopaedic surgery and TCM technology case volumes, with 55 additional orthopaedic procedures and 200 extra TCM interventions recorded (p < 0.001).Total and surgical expenses decreased notably by 42.7% and 26.29%, respectively(p < 0.001), while inpatient expenses for TCM techniques decreased significantly by 32.63% (p < 0.05). Subsidy policies during the C-DRG-based reimbursement system implementation significantly increased the use of appropriate TCM techniques without substantially impacting total expenses. Physicians partially achieved both DRG expenses control and subsidy policy objectives by reducing total expenses and increasing TCM technique usage. The optimal subsidy amount was calculated to be 584.79 RMB, showing a linear relationship with TCM orthopaedic cases, with peak usage aligning with optimal subsidy timing. Conclusion The C-DRG-based reimbursement system and subsidy policies positively influenced the treatment methods of TCM orthopaedic physicians, increasing the number of treated cases and reducing expenses. An optimal subsidy of 584.79 RMB was identified to maximize the number of treated patients, aligning with both DRG expenses control and subsidy policy objectives.